Analisis Penentuan Komposisi Optimum Kargo Dan Pax Pesawat Boeing 787 - 8 Dan Airbus 330 – 900 Pada Rute Jakarta – Dubai Menggunakan Optimasi Linear Programming - Fernando Fransiskus Rotty; Freddy Franciscus; Ericko Chandra (FTK UNSURYA, 2021)
Abstract - The need for airplanes is increasing every day, this is due to the increasing number of passengers and cargo shipments from one area to another. Therefore, airlines need to provide optimal, safe, and efficient cargo and passenger transportation services so that the delivery of goods and passengers can run according to correct procedures. Opportunities in the business of transporting passengers and shipping cargo must be utilized properly by each airline by purchasing planes so that the shipping process from one area to another can quickly arrive at its destination. The purpose of this paper is to find the optimum value of the two aircraft between the Boeing 787-8 and the Airbus 330-900 in terms of the effect on the range, operational costs and to find out which aircraft is more profitable for operating costs on the Jakarta - Dubai route, using linear optimization. programming. Based on the results of the analysis that the optimum point for the calculation of linear programming optimization, the Boeing 787-8 aircraft obtained results (Max payload 41,075 kg, Fuel 6,657 kg, Max Fuel 101,323 kg) where these three results become a limitation for airlines to know the maximum usage of payload and fuel compared Airbus 330-900 aircraft obtained results at the point (Max payload 45,000 kg, Fuel 4,728 kg, Max Fuel 111,272 kg) so that the optimization results are obtained, for Boeing 787-8 aircraft with a max payload of 41,075 kg, max pax 359, max cargo 15,945 kg , compared to Airbus 330-900 with a max payload of 45,000 kg, max pax 460, max cargo 12,800 kg, so it can be concluded that the results of linear programming optimization and the calculation of the operational costs of the Boeing 787-8 aircraft are more optimal with a figure of Rp. 1,541,334,803.96 but in terms of revenue the Airbus 330-900 is bigger than the Boeing 787-8.